The Urgency of Workplace Lactation Rooms and Childcare Facilities: A Public Policy Analysis of Indonesia’s 2024 Child Welfare Law - Windyanisa Afifah Fauziana; Erna Setijaningrum (Journal of Social and Policy Issues, 2025)
This study analyzes how Indonesia’s 2024 Child Welfare Law frames state responsibility and employer obligations in addressing these needs through family-friendly workplace policies. Using a qualitative research design, the study applies a normative policy analysis supported by a comprehensive review of academic literature, policy documents, and relevant regulatory instruments related to child welfare, labor governance, and workplace standards. The findings indicate that the law positions lactation rooms and childcare facilities as essential policy instruments to ensure the fulfillment of children’s basic rights during early childhood while simultaneously promoting workforce productivity and parental work motivation. However, the analysis also reveals significant implementation gaps, particularly in small-scale enterprises and informal workplaces, where financial capacity, infrastructure limitations, and limited policy dissemination hinder compliance. These findings underscore that regulatory mandates alone are insufficient without complementary policy measures, including institutional coordination, technical guidance, and targeted support mechanisms. In conclusion, workplace lactation rooms and childcare facilities represent a critical component of inclusive labor and social policies aimed at strengthening human capital development. The study highlights the urgency of coordinated policy implementation and multi-stakeholder collaboration to achieve equitable, standardized, and sustainable outcomes across regions